WAYS TO APPLY THE PRACTICAL METHOD IN FOREIGN LANGUAGE TEACHING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Our article considers the possibility of using the case method in teaching foreign languages. It provides information about the origin and development of the method. The author shows the requirements for case studies and the advantages and difficulties of the method. In a scientific article, the case study method helps to develop students' communication skills, expand their worldview, teach the formation of general skills, the development of independent exploratory activities, the formation of aesthetic views, and increase their level of competence.